Phosphate uptake in Rhizobium meliloti - Bardin, Sylvie D. (My University, 1997)
The soil bacterium Rhizobium meliloti fixes dinitrogen when associated with root nodules formed on its plant host Medicago sativa (alfalfa). A previously identified locus in R. meliloti 1021, ndvF, is required for nodule invasion and N₂-fixation. Genetic analysis of the locus revealed the presence of four genes, phoCDET which encode an ABC-type phosphate transport system. The transporter had a high affinity for phosphate (Km: 0.2μM) and took up phosphate with low velocity (Vmax: 6.7nmol/min/mg protein). It also showed a low specificity for phosphate as it likely transports phosphonate compounds as well. Expression of transcriptional lacZ fusions to phoD and phoE revealed that these genes were induced upon phosphate limitation and required a functional PhoB protein for their expression. phoCDET mutants grew poorly in MOPS-buffered minimal media containing 2mM Pi as sole phosphorus source, and failed to transport phosphate at concentrations usually found in the soil (1-10μM). This suggested that the symbiotic phenotype associated with mutation in this locus was the result of poor growth in this environment.
Analysis of two classes of mutation that suppressed the Fix⁻ phenotype of phoCDET mutants confirmed the function of this Pi transporter and provided insides into its regulation. Sequence analysis of the ClassI (sfx1) suppressor locus revealed the presence of two genes orfA and pit which likely form an operon. While orfA did not share any significant homology with proteins found in the Data Bank, pit showed homology to phosphate transport systems of various organisms, including the pit gene of Escherichia coli. The sfx1 mutation appeared to be a thymidine deletion in a hepta-thymidine sequence located 80 nucleotides upstream of orfA. orfA pit expression increased in a sfx1 background (compared to the wild type) leading us to hypothesize that suppression by sfx1 occurred by increasing Pi uptake by the Pit (OrfA) phosphate transport system.
The class II suppression mutations (sfx2 and sfx3 alleles) were unable to express the alkaline phosphatase enzyme (AP) suggesting that the mutations probably affect the Pho regulatory genes of R. meliloti. Three AP⁻ Tn5-132 mutants linked in transduction to sfx2 were isolated. Sequence analysis of the DNA flanking these insertions revealed that they were located within the phoU and phoB genes of R. meliloti. These phoU and phoB mutations were able to suppress all the phenotypes associated with phoCDET mutations in a manner similar to sfx2. PhoB was also shown to be required for the uptake and/or metabolism of phosphonate compounds and activation of phoCDET expression. On the other hand, the product of the phoB gene, either directly or indirectly, negatively regulated pit expression in a phosphate dependent manner (i.e. repression under low phosphate conditions and in the phosphate starved environment of phoCDET mutant strains). Suppression of the symbiotic defect of phoCDET mutants by phoUB (sfx2) mutations appeared then to occur by derepressing the pit system of R. meliloti, allowing increased phosphate uptake via this transporter.
Keywords: Biology; Biology